Immunotherapy prospects for acute myeloid leukaemia - Barrett, A J (Blackwell Science Inc, 2010)
While chemotherapy is successful at inducing remission of acute myeloid leukaemia (AML), the disease has a high probability of relapse. Strategies to prevent relapse involve consolidation chemotherapy, stem cell transplantation and immunotherapy. Evidence for immunosurveillance of AML and susceptibility of leukaemia cells to both T cell and natural killer (NK) cell attack and justifies the application of immune strategies to control residual AML persisting after remission induction. Immune therapy for AML includes allogeneic stem cell transplantation, adoptive transfer of allogeneic or autologous T cells or NK cells, vaccination with leukaemia cells, dendritic cells, cell lysates, peptides and DNA vaccines and treatment with cytokines, antibodies and immunomodulatory agents. Here we describe what is known about the immunological features of AML at presentation and in remission, the current status of immunotherapy and strategies combining treatment approaches with a view to achieving leukaemia cure.